HUBUNGAN PERSEPSI SISWA TENTANG PELAJARAN KIMIA DENGAN HASIL BELAJAR KIMIA SISWA SMA NEGERI 9 PEKANBARU - Siti Nazhifah Siti Nazhifah; Jimmi Copriady Jimmi Copriady; Herdini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This Research was aimed to find out the relationship and the magnitude of the relationship between student’s perception of chemistry with chemistry student learning result SMAN 9 Pekanbaru. The kind of research is quantitative-qualitative research which used survey method, correlational and interview. The population of research is all student SMAN 9 Pekanbaru year lesson 2013/2014. The sample consisted of 246 people of class X, XI science, and XII science. Data collection techniques are documentation technique, questionnaire and interview. Data analysis technique is the correlation test. Based on the final calculation result obtained tvalue is 6.817 > ttable is 1.645 it which means that the hypotheses is accepted or with the other word there is relationship between student’s perception of chemistry with chemistry student learning result SMAN 9 Pekanbaru with the magnitude of the relationship is 16%.Keywords : Perception, Chemistry Lesson, Learning Result.